The Effects of Lecturers’ Personality on Students’ Learning Motivation at English Education Study Program of FKIP UKI Toraja - elim trika sudarsih (Teaching English as a Foreign Language Overseas Journal, 2015)
The objectives of the research are; (i) to find out the kinds of lecturers’ personalities they have at English Education Study Program of FKIP UKI Toraja, (ii) to describe whether the lecturers’ personalities affect students’ learning motivation at English Education Study Program of FKIP UKI Toraja, (iii) to describe the personalities which give positive and negative effect to students’ learning motivation. The researcher employed qualitative method. The subjects of this research were the lecturers and students at English Education Study Program of FKIP UKI Toraja. The data of this research was collected by employing recording, observation and interview. The obtained data was analyzed in three major phases are; reduction, displaying, conclusion/ drawing verification. The result of the research revealed that (1) The lecturers’ personalities of the lecturers in teaching English at English Education Study Program of FKIP UKI Toraja are; extrovert, sensing, thinking, feeling and judging. (2) The lecturers’ personalities affect students’ learning motivation in studying English at English Education Study Program of FKIP UKI are extrovert, sensing, thinking, feeling and judging that gave positive and negative effect on students’ learning motivation. (3) The lecturers’ personalities have the positive and negative effect on students’ learning motivation.